THE FORMATION OF THE ASSESSMENT MECHANISMS OF FOREIGN LANGUAGE TEACHERS’ PROFESSIONAL ACTIVITIES IN THE UNIVERSITIES OF UZBEKISTAN - Azizov, Ulugbek (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
Historically, teaching foreign languages at the universities of Uzbekistan has been based on the ability to develop students’ linguistic competence. Linguistic competence that is taught by applying (Grammar-Translation Method - GMT) has been a key element in assessing the professional activities of foreign language university teachers in Uzbekistan. In this regard, these teachers used to be asked to develop students’ grammatical, syntactical and stylistic literacy. After the implementation of the Common European Framework of References — CEFR in Uzbekistan in 2012, foreign language university teachers have stared to be required to follow the principles of CEFR. According to CEFR, linguistic, sociolinguistic, pragmatic and strategic competences are considered to be important in developing students’ ability to communicate effectively in foreign languages in authentic situations. Concordantly, an assessment of the professional activities of university teachers in Uzbekistan has started to be based on the ability of these teachers to develop students’ competences not only in linguistics, but also in sociolinguistics, pragmatics, and strategics. In this article, we will discuss these communicative competences, which have started to be applied after 2012 in assessing the professional activities of foreign language university teachers in Uzbekistan.